The Influence of Family Communication Patterns on Adolescents' Decision-Making Process - Chen, Yi-Chieh (2008)
While studies around children and adolescents' influence on family purchasing have been greatly focused on, little investigation has been on family communication patterns influencing on children and adolescents' decision-making process. In order to fill the gap, this study examines the effect of family communication patterns on teenagers' (aged 16-18) decision-making process. The results indicate that in the information seeking stage, the adolescents in pluralistic and consensual family communications score higher in acquiring information from mothers than other teens. However, gaining information from fathers occurs to be less preferred in all types of family communication clusters. In the evaluation and purchasing stages, the teens in all family communication categories do not like to choose the products preferred by fathers and mothers; in addition, they are unlikely to ask fathers and mothers to purchase products with them either. With regard to the adolescents in protective and consensual family communications, they share some common ground in the entire decision-making process. To be more precise, they have higher desire to gain information from TV advertising, to assess products by well-known brand names, and to ask friends to go shopping with.